2022
DOI: 10.3390/cells11233893
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Derived Exosomal GOT1 Suppresses Tumor Cell Ferroptosis to Accelerate Pancreatic Cancer Progression by Activating Nrf2/HO-1 Axis via Upregulating CCR2 Expression

Abstract: Recently, evidence has shown that GOT1 expression is upregulated in pancreatic cancer tissues and promotes cancer development, but the specific mechanism remains unclear. We found that GOT1 expression was upregulated in pancreatic cancer cell-derived exosomes. When PANC-1 cells were incubated with exosomes alone or transfected together with si-GOT1, we found that exosomes enhanced cell proliferation, invasion and migration, promoted ferroptosis, and si-GOT1 reversed the effects of exosomes. The results of onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Except for overloaded Fe concentration, excessive lipid peroxidation is an outstanding feature of ferroptosis. Accordingly, Nrf2/HO‐1/GPX4 was regarded as one of the most concerned anti‐ferroptosis pathways in tumours and non‐cancerous tissues 45–47 . In this study, we reported that Nrf2/HO‐1 was activated by cancer cell‐derived exosomal HSPB1 in hypoxic pancreatic cancer cells via FUS protein, and knockdown of HSPB1 or FUS caused suppression of Nrf2/HO‐1, increased the level of the ferroptosis fuel P450 oxidases, 48,49 and inhibited pancreatic cancer progression in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…Except for overloaded Fe concentration, excessive lipid peroxidation is an outstanding feature of ferroptosis. Accordingly, Nrf2/HO‐1/GPX4 was regarded as one of the most concerned anti‐ferroptosis pathways in tumours and non‐cancerous tissues 45–47 . In this study, we reported that Nrf2/HO‐1 was activated by cancer cell‐derived exosomal HSPB1 in hypoxic pancreatic cancer cells via FUS protein, and knockdown of HSPB1 or FUS caused suppression of Nrf2/HO‐1, increased the level of the ferroptosis fuel P450 oxidases, 48,49 and inhibited pancreatic cancer progression in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, Guo et al found that GOT1 protein enrichment in exosomes secreted by pancreatic cancer cells inhibits ferroptosis of cancer cells and promotes tumour development. In terms of mechanism, GOT1 can upregulate the expression of the C–C motif chemokine receptor-2 (CCR2), thereby activating the Nrf2/HO-1 axis to resist ferroptosis in cancer cells [ 79 ].…”
Section: Mechanism and Application Of Exosome-regulated Ferroptosismentioning
confidence: 99%
“…The C–C motif chemokine receptor‐2 (CCR2) is reportedly highly expressed in cancer cells and correlated with poor prognosis 66 . It was shown that glutamic‐oxaloacetic transaminase 1 (GOT1) from tumor‐derived exosomes could upregulate CCR2 to stimulate the Nrf2‐HO‐1 pathway, resulting in increased GPX4 and decreased ROS, MDA, and Fe 2+ levels to hinder ferroptosis and eventually promoted tumor cell migration and invasion 67 . Therefore, targeting the exosome‐mediated Nrf2‐HO‐1 axis represents a potential approach to regulate ferroptosis in tumor cells.…”
Section: The Mechanisms Of Exosomes In Regulating Ferroptosismentioning
confidence: 99%